Improving the coverage and accuracy of syphilis testing: The development of a novel rapid, point-of-care test for confirmatory testing of active syphilis infection and its early evaluation in China and South Africa. (July 2020) - Pham, Minh D.; Wise, Amy; Garcia, Mary L.; Van, Huy; Zheng, Shuning; Mohamed, Yasmin; Han, Yan; Wei, Wan-Hui; Yin, Yue-Ping; Chen, Xiang-Sheng; Dimech, Wayne; Braniff, Susie; et al.
Abstract: Background: Current point-of-care tests (POCT) for syphilis, based on the detection of Treponema pallidum (TP) total antibodies, have limited capacity in distinguishing between active and past/treated syphilis. We report the development and early evaluation of a new prototype POCT based on the detection of TP-IgA antibodies, a novel biomarker for active syphilis. Methods: The TP-IgA POCT (index test) was developed in response to the World Health Organisation (WHO) target product profile (TPP) for a POCT for confirmatory syphilis testing. Two sub-studies were conducted consecutively using 458 pre-characterised stored plasma samples in China (sub-study one, addressing the criteria for the WHO TPP), and 503 venous blood samples collected from pregnant/postpartum women in South Africa (sub-study two, addressing potential clinical utility). Performance of the index test was assessed against standard laboratory-based serology using a combination of treponemal (TPHA) and non-treponemal (rapid plasma reagin [RPR]) tests. Findings: In sub-study one, the index test demonstrated 96·1% (95%CI=91·7%-98·5%) sensitivity and 84·7% (95%CI=80·15–88·6%) specificity for identification of active syphilis (TPHA positive, RPR positive). It correctly identified 71% (107/150) samples of past-treated syphilis (TPHA positive, RPR negative). In sub-study two, the index test achieved 100% (95%CI=59%-100%) sensitivity for active syphilis and correctly identified all nine women with past syphilis. Interpretation: The TP-IgA POCT has met the WHO TPP for a POCT for diagnosis of active syphilis and demonstrated its potential utility in a clinical setting. Future studies are warranted to evaluate field performance of the final manufactured test. Funding: Saving Lives at Birth: Grand Challenge for Development, Thrasher Research Fund, and the Victorian Government Operational Infrastructure Scheme.